TANGGUNG JAWAB DEBITUR ATAS PENGALIHAN OBJEK PEMBIAYAAN SECARA SEPIHAK PADA PT BATAVIA PROSPERINDO FINANCE TBK PEKANBARU - Ayu Kristiani P; Maryati Bachtiar; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Legal consequences arising when violating the agreement in the financing of four-wheeled vehicle credit is included in the act against the law. In the city of Pekanbaru there are 44 finance companies and 41 registered companies in the OJK. One of the financing companies in Pekanbaru is at PT Batavia Prosperindo Finance Tbk Pekanbaru. Article 23 Paragraph (2) of Law Number 42 Year 1999 concerning Fiduciary Guarantee states that: "Debtors are prohibited from transferring, mortgaging, or renting out to other parties objects that are objects of Fiduciary Security that are not inventories, except with prior written approval from Fiduciary Recipients ". However, there was a unilateral transfer of financing by PT Batavia Prosperindo Finance Tbk Pekanbaru. Therefore, the purpose of writing this thesis, namely: first, to determine the debtor's responsibility for the transfer of the object of financing unilaterally at PT Batavia Prosperindo Finance Tbk Pekanbaru. Second, to find out the efforts to resolve the transfer of financing objects unilaterally at PT Batavia Prosperindo Finance Tbk Pekanbaru.This type of research can be classified as empirical or sociological legal research, because in this study the writer directly conducts research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted at PT Batavia Prosperindo Finance Tbk Pekanbaru. Sources of data used, namely: primary data, secondary data and tertiary data. Data collection techniques in this study were Observation, Interview, and Literature Study.The conclusion that can be obtained from the results of the first study, the loss experienced by PT Batavia Prosperindo Finance Tbk Pekanbaru is not accounted for by the debtor who carried out the transfer of the object unilaterally. Though must be responsible in accordance with the agreement between the Debtor and the Creditors. Second, the effort taken to settle the default is an effort to settle litigation, namely the settlement of a dispute in court, by making a report / complaint to the Police in requesting fulfillment of compensation from the debtor conducting the default. The author's suggestion is that to PT Batavia Prosperindo Finance Tbk Pekanbaru, it is better in entering into a financing agreement the company provides a prior understanding of the debtor about the consequences of the agreement, so that in the future does not harm the parties or one of the parties. The debtor should read carefully and thoroughly the contents of the agreed financing agreement, so that they know their respective rights and obligations.Keywords: Responsibility - Transfer of Objects of Financing Unilaterally